A micro-mechanical constitutive model for cracked plies of laminated composites considering the constraint effect of the adjacent plies. Issue 25 (12th October 2022) - Yuan, Mingqing; Zhao, Haitao; Peng, Yahui; Liu, Xinyang; Yao, Yongtao; Chen, Ji'an
Abstract: Three types of representative unit cell (RUC) of [± θ /904 ]S composite laminates and cracked plies were created to obtain the constitutive model of the cracked plies and to compare their accuracy of the calculation. The RUCs represent the damaged laminates, cracked plies, and cracked plies with additional constraints. A correction factor was defined to improve the accuracy of transverse modulus estimation using the RUC of cracked plies with constraints. The correction factor and numerical results were discussed to illustrate the constraint effect of the adjacent plies on the cracked plies in terms of stiffness, orientation, and thickness.